The Influence of Leadership Style, Work Environment, and Employee Satisfaction as Intervening Variable towards Employee Performance in PT X - Christy, Erica; Dewi, Liliana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to examine and analyze the variables that influence employee performance. The variables studied include leadership style, work environment, and job satisfaction. The approach to this research is quantitative method, and focuses on the analysis of variables that affect employee performance with a survey method approach using a questionnaire. The data collected from the questionnaire will be analyzed statistically using Partial Least Square-Structural Equation Modeling (PLS-SEM). The population in this study are all employees in the Operations Finance division at PT X under the leadership of the Director of Operations Finance. This research was conducted on 112 respondents with a purposive sampling method. The results of the study state that the variables of leadership style and work environment have a significant effect on the variable of job satisfaction, the variable of leadership style and work environment has a significant effect on the variable of employee performance, and the variable of job satisfaction has a significant effect on the variable of employee performance. This shows that leadership style and work environment have an impact on job satisfaction which in the end the expected employee performance is achieved.